Institution and Legal Aspect Based River Water Quality Management - Namara, Idi; M Hartono, Djoko; Latief, Yusuf; Sarwanto Moersidik, Setyo (International Journal of Engineering and Technology, 2018)
About 75% of rivers in Indonesia are experiencing severe pollution. The pollution comes from domestic waste. One of the important rivers in Indonesia that is experiencing pollution is the Cisadane River. The Cisadane River issues in Tangerang are erosion, sedimentation, not yet controlled public space, availability water, and water quality. The background of this research is the existence of water quality problems Cisadane Tangerang City of Banten Province. There are many institutions that manage the Cisadane watershed, but the effectiveness of these institutions in solving environmental problems in the Cisadane watershed is ineffective. Similarly, current regulations have not been effectively implemented. The purpose of this study is to determine the authority and agencies that manage the Cisadane watershed in Tangerang, examining the effectiveness of cooperation among agencies, seeking the most effective alternative institutions in Cisadane water quality management, as well as optimizing the implementation of regulations. This research is a qualitative research, this research also is multi case and explorative, so this research uses three stages of research, previous study phase study, focus group discussion and data analysis. The conclusion of this research is to get the best and effective alternative institution in managing Cisadane River and to strengthen regulation or law.